Molecular Mechanics Study of Cyclic and Unsymmetrical Diborane(4) Compounds - Rendtorff Birrer, Nicolás Maximiliano (2003)
The results of a theoretical study on the structure of some diborane(4) compounds are presented in order to analyze the ralative stabilities of the 1,1- and 1,2-isomers. Using the molecular mechanics method, characteristic distances and angles have been calculated and compared with available experimental data. In order to rationalize the results, different energy components are discussed in a comparative fashion. A fairly satisfactory agreement between the theoretical and experimental data have been found. Some possible extensions are pointed out to complement this kind of analysis.